Method for manufacturing self-fluxing alloy coating, self-fluxing alloy coating, component, and powder material
A balanced powder composition and fusing treatment form a self-fluxing alloy film on continuous casting rolls, addressing wear and thermal shock resistance issues in existing thermal spray coatings.
Patent Information
- Application Number
- JP2024546188
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-01-16
- Filing Date
- 2024-01-12
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2044-01-12
AI Technical Summary
Existing thermal spray coating layers for continuous casting rolls, containing Ni-based or Co-based self-fluxing alloys and carbides like tungsten carbide, lack sufficient wear resistance and thermal shock resistance.
A method involving the application of a powder mixture comprising a first powder (Ni-based or Co-based self-fluxing alloy), a second powder (carbide ceramics or carbide cermets), and a third powder (Cr, Mo, Fe, Ni, or Co-based alloys) onto a base material, followed by a fusing treatment to form a self-fluxing alloy coating, optimizing the composition to achieve balanced wear and thermal shock resistance.
The method produces a self-fluxing alloy film with enhanced wear resistance and thermal shock resistance, suitable for continuous casting rolls, by ensuring appropriate proportions of the powder components and a fusing treatment to improve adhesion and density.
Smart Images

Figure 0007618110000001 
Figure 0007618110000002 
Figure 0007618110000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a self-fluxing alloy coating, as well as to self-fluxing alloy coatings, components, and powder materials formed using the method. [Background technology]
[0002] In the continuous casting method, molten steel is poured into a water-cooled copper mold, and the cast piece is pulled out with only the surface solidified. The cast piece is supported by rolls and cooled with water sprays to gradually solidify it. The continuous casting rolls used in such continuous casting equipment are used in a harsh environment where rapid heating and cooling are repeated, and are damaged by wear during the transportation of the cast piece. Therefore, such continuous casting rolls are required to have wear resistance.
[0003] For example, Patent Document 1 proposes a breakage-resistant and wear-resistant roll for continuous casting, which is formed by spraying and cladding a Ni-based or Co-based self-fluxing alloy onto the barrel surface of a stainless steel roll and then subjecting the roll to a melting heat treatment.
[0004] Moreover, Patent Document 2 proposes a continuous casting roll having a thermally sprayed coating layer containing a Ni-based or Co-based self-fluxing alloy and a carbide such as tungsten carbide. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Japanese Patent Application Publication No. 57-203765 [Patent Document 2] JP 2006-263807 A Summary of the Invention [Problem to be solved by the invention]
[0006] The breakage-resistant and wear-resistant roll for continuous casting proposed in Patent Document 1 has a thermally sprayed build-up layer of Ni-based or Co-based self-fluxing alloy-type sprayed metal on the barrel surface of a stainless steel roll, but its wear resistance is insufficient.
[0007] Patent Document 2 describes that by adding a carbide such as tungsten carbide to a Ni-based or Co-based self-fluxing alloy, a thermal spray coating layer made of a self-fluxing alloy with excellent wear resistance can be formed. It also describes that by extremely reducing the C content in the self-fluxing alloy, the thermal spray coating layer does not become hard and brittle, and the generation of a carburized layer during fusing processing is suppressed, making it possible to form a thermal spray coating layer with little risk of peeling.
[0008] However, as a result of research conducted by the present inventors, it has been found that even a thermal spray coating layer containing a Ni-based or Co-based self-fluxing alloy and a carbide such as tungsten carbide, as in Patent Document 2, does not have sufficient thermal shock resistance.
[0009] The present invention has been made in consideration of the above problems, and an object of the present invention is to provide a method for forming a self-fluxing alloy coating on a substrate that has both wear resistance and thermal shock resistance. [Means for solving the problem]
[0010] The method for producing a self-fluxing alloy film of the present invention is characterized by carrying out the following steps (a) and (b). (a) spraying a powder material, which is a mixture of a first powder, a second powder, and a third powder, onto a substrate to form a thermal spray coating on the substrate; (b) A step of fusing the thermal spray coating to form a self-fluxing alloy coating.
[0011] Furthermore, the method for producing a self-fluxing alloy coating of the present invention has the following features (1) and (2). (1) The first powder is one or more types of self-fluxing alloys selected from the group consisting of Ni-based self-fluxing alloys and Co-based self-fluxing alloys, and the self-fluxing alloys contain 0.8 to 4.5 mass % B and 1.5 to 5.0 mass % Si. The second powder is one or more types selected from the group consisting of carbide ceramics and carbide cermets. The third powder is one or more types selected from the group consisting of Cr, Mo, Fe, Ni, Co, and alloys having any of them as main components (however, for alloys having Ni as a main component and alloys having Co as a main component, the Ni-based self-fluxing alloys and Co-based self-fluxing alloys defined in the first powder are excluded). (2) When the most abundant element by mass in the third powder is Cr, Fe, Ni, or Co, the powder material contains 45 to 65 mass% of the first powder, 5 to 35 mass% of the second powder, and 5 to 50 mass% of the third powder, and when the most abundant element by mass in the third powder is Mo, the powder material contains 70 to 85 mass% of the first powder, 5 to 25 mass% of the second powder, and 5 to 25 mass% of the third powder.
[0012] Moreover, preferred conditions for the method for producing a self-fluxing alloy film of the present invention include the following (3) to (5). (3) The first powder contains 2.5 to 4.0 mass % B and 3.0 to 5.0 mass % Si. (4) The second powder is a tungsten carbide cermet, and the sum of the W content and the C content is 70 mass % or more. (5) The third powder contains 10 to 30 mass % of Cr or 5 to 20 mass % of Mo.
[0013] Further, the method for producing a self-fluxing alloy film of the present invention can be applied to the following items (6) to (10). (6) A self-fluxing alloy coating formed by using any one of the manufacturing methods (1) to (5) above. (7) A component for steel-making equipment, having a self-fluxing alloy coating formed on a substrate by the manufacturing method according to any one of (1) to (5). (8) A component part of an iron-making facility, a steel-making facility, or a non-ferrous metal refining facility, having a self-fluxing alloy coating formed on a substrate by the manufacturing method according to any one of (1) to (5) above. (9) A component part for hot rolling equipment for steel or non-ferrous metals, the component part having a self-fluxing alloy coating formed on a substrate by the manufacturing method according to any one of (1) to (5) above. (10) A component for continuous casting equipment, having a self-fluxing alloy coating formed on a substrate by the manufacturing method according to any one of (1) to (5) above.
[0014] Moreover, the powder material of the present invention is a powder material obtained by mixing a first powder, a second powder, and a third powder, and has the following characteristics (11) and (12). (11) The first powder is one or more types of self-fluxing alloys selected from the group consisting of Ni-based self-fluxing alloys and Co-based self-fluxing alloys, and the self-fluxing alloys contain 0.8 to 4.5 mass % B and 1.5 to 5.0 mass % Si. The second powder is one or more types selected from the group consisting of carbide ceramics and carbide cermets. The third powder is one or more types selected from the group consisting of Cr, Mo, Fe, Ni, Co, and alloys having any of them as main components (however, for alloys having Ni as a main component and alloys having Co as a main component, the Ni-based self-fluxing alloys and Co-based self-fluxing alloys defined in the first powder are excluded). (12) When the most abundant element by mass in the third powder is Cr, Fe, Ni, or Co, the powder material contains 45 to 65 mass% of the first powder, 5 to 35 mass% of the second powder, and 5 to 50 mass% of the third powder, and when the most abundant element by mass in the third powder is Mo, the powder material contains 70 to 85 mass% of the first powder, 5 to 25 mass% of the second powder, and 5 to 25 mass% of the third powder. Effect of the Invention
[0015] According to the present invention, it is possible to form a self-fluxing alloy coating on a substrate, which has both abrasion resistance and thermal shock resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] An embodiment of the method for producing a self-fluxing alloy film and the powder material according to the present invention will be described below.
[0017] The method for producing a self-fluxing alloy film according to this embodiment includes the following steps (a) and (b). (a) spraying a powder material, which is a mixture of a first powder, a second powder, and a third powder, onto a substrate to form a thermal spray coating on the substrate; (b) A process of fusing the thermal spray coating to form a self-fluxing alloy coating.
[0018] In the step (a), a powder material obtained by mixing a first powder, a second powder, and a third powder is sprayed onto a substrate to form a thermal spray coating on the substrate.
[0019] The substrate may be, for example, a metal substrate, and is not particularly limited and may be any substrate. The metal substrate may be, for example, a stainless steel substrate. The substrate in the present invention may also include a substrate having a coating applied to its surface. Such a coating may be, for example, an iron-chromium-based hardfacing layer.
[0020] The powder material is a mixture of the first powder, the second powder, and the third powder, and is a material for self-fluxing alloy thermal spraying. The powder material may contain other powder components than the first powder, the second powder, and the third powder, but preferably the total amount of the first powder, the second powder, and the third powder is 80 mass% or more of the entire powder, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably the powder is composed only of the first powder, the second powder, the third powder, and inevitable impurities.
[0021] The first powder is one or more kinds of self-fluxing alloys selected from the group consisting of Ni-based self-fluxing alloys and Co-based self-fluxing alloys, and the self-fluxing alloy contains 0.8-4.5 mass% B and 1.5-5.0 mass% Si. When the contents of B and Si are within the above ranges, the melting temperature of the alloy is lowered, self-fluxing properties are imparted, and the workability of the fusing process in step (b) is improved. More preferably, the self-fluxing alloy contains 2.5-4.0 mass% B and 3.0-5.0 mass% Si. When the contents of B and Si are within these ranges, the above-mentioned effects are more easily obtained.
[0022] The first powder is not particularly limited as long as it satisfies the above requirements, but may be selected from the group consisting of one, two, three, four, five, six, seven, eight, and nine types of Ni-based self-fluxing alloys, or may be selected from the group consisting of one and two types of Co-based self-fluxing alloys, as shown in Table 1 below. Such a first powder plays a role in particular in improving the thermal shock resistance of the self-fluxing alloy coating. In Table 1, the portion described as "below" may not contain the element.
[0023] [Table 1]
[0024] The second powder is one or more selected from the group consisting of carbide ceramics and carbide cermets. Examples of carbide ceramics include tungsten carbide (WC), chromium carbide (Cr3C2, etc.), and niobium carbide (NbC), and examples of carbide cermets include those obtained by compounding these carbide ceramics with metals. Such second powders play a role in improving the wear resistance of the self-fluxing alloy coating. The second powder is particularly preferably a tungsten carbide cermet. The tungsten carbide cermet may be one that is normally used in the relevant technical field. For example, the tungsten carbide cermet may be WC-Co, WC-Co-Cr, or WC-Ni. In addition, the tungsten carbide cermet preferably has a total content of W and C of 70% by mass or more relative to the entire tungsten carbide cermet. When the total content of W and C is 70% by mass or more, the wear resistance of the self-fluxing alloy coating is improved.
[0025] The third powder is one or more selected from the group consisting of Cr, Mo, Fe, Ni, Co, and alloys having any of them as the main component. However, the alloys having Ni as the main component (hereinafter also referred to as "Ni-based alloys") and the alloys having Co as the main component (hereinafter also referred to as "Co-based alloys") are materials other than the Ni-based self-fluxing alloys and Co-based self-fluxing alloys defined in the first powder. In this specification, the main component refers to the component having the highest content ratio among all components on a mass basis. In addition, the main component is preferably 40 mass% or more of all components, more preferably 50 mass% or more, and even more preferably 60 mass% or more. The Ni-based alloys that can be used as the third powder can be selected from the group consisting of Monel K500, Monel 400, Hastelloy B, Hastelloy C276, Hastelloy C22, Inconel 600, Inconel 625, Incoloy 800, and Incoloy 825, for example. The Co-based alloy usable as the third powder may be selected from the group consisting of, for example, Stellite 6, Stellite 12, Stellite 21, Stellite 31, Triballoy T-400, and Triballoy T-800. The Fe-based alloy usable as the third powder may be selected from the group consisting of, for example, SUS316L, SUS304, SUS310S, SUS430, SUS420J2, and S45C. The Mo-based alloy usable as the third powder may be selected from the group consisting of, for example, MoSi2 and Mo-Ti-Zr-C. (TZM alloy). The third powder preferably contains 10 to 30 mass % of Cr or 5 to 20 mass % of Mo. In this way, the Cr or Mo in the third powder bonds with the B contained in the first powder to form an intermetallic compound, improving the wear resistance of the self-fluxing alloy coating. In addition, the Cr, Mo, Fe, Ni, or Co used as the third powder may contain one or more other metal components as impurities in addition to these metal components.
[0026] When the element most abundant in the third powder by mass is Cr, Fe, Ni, or Co, the powder material contains 45 to 65 mass% of the first powder, 5 to 35 mass% of the second powder, and 5 to 50 mass% of the third powder. If the content of the first powder is less than 45 mass%, the melting property of the self-fluxing alloy spray coating is insufficient, and the quality of the self-fluxing alloy coating after fusing may be poor. On the other hand, if the content of the first powder is more than 65 mass%, the self-fluxing alloy coating becomes hard and brittle, and the thermal shock resistance of the coating is insufficient. Furthermore, if the content of the second powder is less than 5 mass%, the wear resistance of the self-fluxing alloy coating is insufficient. On the other hand, if the content of the second powder is more than 35 mass%, the self-fluxing alloy coating becomes hard and brittle, and the thermal shock resistance of the coating is insufficient. Furthermore, if the content of the third powder is less than 5 mass%, the third powder cannot fully exert its effect as a binder, and the thermal shock resistance of the self-fluxing alloy coating is insufficient. On the other hand, if the content of the third powder exceeds 50 mass%, the wear resistance of the self-fluxing alloy coating is insufficient. When each powder contains multiple materials, the total content of each is defined as the total content of each. For example, Inconel 625 and Stellite 21 are both classified as third powders, but when the powder material contains both of these, the total of these may account for 5 to 50 mass% of the entire powder material.
[0027] When the most abundant element in the third powder is Mo, the powder material contains 70 to 85 mass% of the first powder, 5 to 25 mass% of the second powder, and 5 to 25 mass% of the third powder. If the content of the first powder is less than 70 mass%, the melting property of the self-fluxing alloy spray coating is insufficient, and the quality of the self-fluxing alloy coating after fusing may be poor. On the other hand, if the content of the first powder is more than 85 mass%, the self-fluxing alloy coating becomes hard and brittle, and the thermal shock resistance of the coating is insufficient. Furthermore, if the content of the second powder is less than 5 mass%, the wear resistance of the self-fluxing alloy coating is insufficient. On the other hand, if the content of the second powder is more than 25 mass%, the self-fluxing alloy coating becomes hard and brittle, and the thermal shock resistance of the coating is insufficient. Furthermore, if the content of the third powder is less than 5 mass%, the third powder cannot fully exert its effect as a binder, and the thermal shock resistance of the self-fluxing alloy coating is insufficient. On the other hand, if the content of the third powder exceeds 25 mass%, the wear resistance of the self-fluxing alloy coating is insufficient. When each powder contains multiple materials, the total content of each is defined as the total content of each. For example, Mo and MoSi2 are both classified as third powders, but when the powder material contains both of these, the total content of these may be 5 to 25 mass% of the entire powder material.
[0028] The thermal spraying in step (a) can be carried out by any thermal spraying method, such as powder flame spraying, plasma spraying, preferably atmospheric plasma spraying.
[0029] In step (a), the shape and dimensions of the substrate are not particularly limited and may be any desired shape and dimensions. The thermal spray coating formed on the substrate in step (a) has a thickness of, for example, 500 to 5000 μm.
[0030] In step (b), the thermal spray coating formed in step (a) is subjected to a fusing treatment (remelting treatment) to form a self-fluxing alloy coating.
[0031] The fusing treatment is performed on the thermal spray coating formed on the substrate in step (a). The fusing treatment is not particularly limited, but can be performed under conditions generally used in the field of self-fluxing alloy thermal spraying, for example, by increasing the temperature of the coating to 950°C to 1200°C in air or a non-oxidizing atmosphere. This fusing treatment reduces pores in the thermal spray coating, densifies the thermal spray coating, and forms a diffusion layer between the substrate and the thermal spray coating, resulting in a self-fluxing alloy coating with high adhesion. The fusing treatment temperatures for the Ni-based self-fluxing alloy and the Co-based self-fluxing alloy defined in the first powder are almost the same, and can be selected according to the environment in which the coating is used.
[0032] In the self-fluxing alloy coating formed in step (b), the thickness of the diffusion layer formed between the substrate and the thermal spray coating is, for example, 50 to 500 μm. The self-fluxing alloy coating also contains the substrate components in addition to the components of the first to third powders. The substrate components are preferably 10 mass% or less. That is, the self-fluxing alloy coating formed in step (b) contains the components derived from the first to third powders and the components derived from the substrate, and the total amount of the components derived from the first to third powders and the components derived from the substrate is preferably 80 mass% or more of the entire coating, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably only the components derived from the first to third powders, the components derived from the substrate, and inevitable impurities. The type of inevitable impurities is not particularly limited, and may be, for example, impurities mixed from the outside during steps (a) and (b).
[0033] The wear amount of the self-fluxing alloy coating formed in step (b) is, for example, 0 to 200 mg / 2000 times, as measured by the Suga abrasion test described below. If the wear amount of the self-fluxing alloy coating exceeds 200 mg / 2000 times, the abrasion resistance of the coating is insufficient. Furthermore, the wear amount of the self-fluxing alloy coating formed in step (b) is preferably 0 to 100 mg / 2000 times, more preferably 0 to 50 mg / 2000 times, as measured by the Suga abrasion test.
[0034] The thermal shock resistance of the self-fluxing alloy coating formed in step (b) is rated as ◯ or Δ when measured by a thermal shock resistance test described below. If the thermal shock resistance of the self-fluxing alloy coating is rated as ×, the thermal shock resistance of the coating is insufficient.
[0035] An example of a method for manufacturing a self-fluxing alloy coating in this embodiment will be described. First, the first powder, the second powder, and the third powder are weighed and transferred to a container, and these powders are mixed to prepare a powder material. Next, the prepared powder material is used to perform thermal spraying on the surface of a substrate to form a thermal spray coating on the substrate. For example, in the case of atmospheric pressure plasma spraying, a voltage is applied between the cathode and the anode to generate a DC arc. Next, a working gas such as argon gas is fed to this DC arc to ionize the working gas, generating a high-temperature, high-velocity plasma jet. Then, the powder material is fed into the generated plasma jet with argon gas or the like, and sprayed onto the substrate to form a thermal spray coating (step (a)). Finally, the thermal spray coating formed on the substrate is heated, for example, in an atmosphere with a flame at about 3000°C to raise the coating temperature to about 1000°C, and fusion is performed to form a self-fluxing alloy coating (step (b)). In this manner, a self-fluxing alloy film having both abrasion resistance and thermal shock resistance can be manufactured. However, the method for manufacturing the self-fluxing alloy film in this embodiment is not limited to the above example. EXAMPLES
[0036] EXAMPLES Examples to which the present invention is applied and comparative examples will be described below. These examples are merely illustrative of the present invention and are not intended to limit the scope of the invention.
[0037] [1st powder] As the first powder, a powder of a Ni-based self-fluxing alloy (hereinafter also referred to as "Ni-3B-4.4Si") (manufactured by Fukuda Metal Foil & Powder Co., Ltd.) containing 3.05 mass% B, 0.02 mass% C, 4.43 mass% Si, and the remainder Ni (i.e., Ni is 92.50 mass%) was prepared.
[0038] [Second powder] As the second powder, a powder of tungsten carbide cermet (hereinafter also referred to as "WC-12Co") containing 5.40 mass% C, 11.70 mass% Co, and the remainder W (i.e., 82.90 mass% W) (manufactured by Sumitomo Metal Mining Co., Ltd.) was prepared.
[0039] [Third powder] As the third powder, a powder of Ni-based alloy (hereinafter also referred to as "Inconel 625") containing 0.46 mass% Si, 21.20 mass% Cr, 0.46 mass% Fe, 3.57 mass% Nb, 9.10 mass% Mo, and the remainder Ni (i.e., Ni is 65.21 mass%) (manufactured by Höganäs) was prepared. Also, as the third powder, a powder of Fe-based alloy (hereinafter also referred to as "SUS316L") containing 0.02 mass% C, 0.91 mass% Si, 17.27 mass% Cr, 12.75 mass% Ni, and the remainder Fe (i.e., Fe is 69.05 mass%) (manufactured by Sanyo Special Steel Co., Ltd.) was prepared. As the third powder, a powder of a Co-based alloy (hereinafter also referred to as "Stellite 21") containing 0.26 mass% C, 1.25 mass% Si, 26.92 mass% Cr, 1.32 mass% Fe, 3.02 mass% Ni, 6.05 mass% Mo, and the balance being Co (i.e., 61.18 mass% Co) (manufactured by Sanyo Special Steel Co., Ltd.) was also prepared. Furthermore, as the third powder, a powder of Mo containing 0.29 mass% C, 0.03 mass% Fe, and the balance being Mo (i.e., 99.68 mass% Mo) (manufactured by Powrex Corporation) was also prepared.
[0040] The chemical compositions of the first, second, and third powders prepared in this example are shown in Table 2 below.
[0041] [Table 2]
[0042] [Example 1] A powder material was prepared containing 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 10 mass% of WC-12Co (WC cermet) as the second powder, and 30 mass% of Inconel 625 as the third powder. Next, atmospheric plasma spraying was performed on a 50 mm x 50 mm x 30 mmt S45C substrate using the prepared powder material under the following conditions to form a sprayed coating on the substrate. Thereafter, the temperature of the sprayed coating was raised to about 1000°C and a fusing process was performed to form a self-fluxing alloy coating, and a test piece of Example 1 was produced. Current value: 400A Argon gas flow rate: 36NLPM
[0043] [Example 2] The test pieces of Example 2 were prepared in the same manner as Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 15 mass% of WC-12Co (WC cermet) as the second powder, and 25 mass% of Inconel 625 as the third powder.
[0044] [Example 3] The test pieces of Example 3 were prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 20 mass% of WC-12Co (WC cermet) as the second powder, and 20 mass% of Inconel 625 as the third powder.
[0045] [Example 4] The test pieces of Example 4 were prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 25 mass% of WC-12Co (WC cermet) as the second powder, and 15 mass% of Inconel 625 as the third powder.
[0046] [Example 5] The test pieces of Example 5 were prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 30 mass% of WC-12Co (WC cermet) as the second powder, and 10 mass% of Inconel 625 as the third powder.
[0047] [Example 6] The test pieces of Example 6 were prepared in the same manner as in Example 1, except that a powder material was used that contained 50 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 20 mass% of WC-12Co (WC cermet) as the second powder, and 30 mass% of Inconel 625 as the third powder.
[0048] [Example 7] The test pieces of Example 7 were prepared in the same manner as in Example 1, except that a powder material was used that contained 50 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 25 mass% of WC-12Co (WC cermet) as the second powder, and 25 mass% of Inconel 625 as the third powder.
[0049] [Example 8] The test pieces of Example 8 were prepared in the same manner as in Example 1, except that a powder material was used that contained 50 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 30 mass% of WC-12Co (WC cermet) as the second powder, and 20 mass% of Inconel 625 as the third powder.
[0050] [Example 9] The test pieces of Example 9 were prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 10 mass% of WC-12Co (WC cermet) as the second powder, and 30 mass% of SUS316L as the third powder.
[0051] [Example 10] The test piece of Example 10 was prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 20 mass% of WC-12Co (WC cermet) as the second powder, and 20 mass% of SUS316L as the third powder.
[0052] [Example 11] The test piece of Example 11 was prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 30 mass% of WC-12Co (WC cermet) as the second powder, and 10 mass% of SUS316L as the third powder.
[0053] [Example 12] The test pieces of Example 12 were prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 10 mass% of WC-12Co (WC cermet) as the second powder, and 30 mass% of Stellite 21 as the third powder.
[0054] [Example 13] The test piece of Example 13 was prepared in the same manner as Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 20 mass% of WC-12Co (WC cermet) as the second powder, and 20 mass% of Stellite 21 as the third powder.
[0055] [Example 14] The test piece of Example 14 was prepared in the same manner as in Example 1, except that a powder material was used that contained 60 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 30 mass% of WC-12Co (WC cermet) as the second powder, and 10 mass% of Stellite 21 as the third powder.
[0056] [Example 15] The test piece of Example 15 was prepared in the same manner as in Example 1, except that a powder material was used that contained 80 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 5 mass% of WC-12Co (WC cermet) as the second powder, and 15 mass% of Mo as the third powder.
[0057] [Example 16] The test piece of Example 16 was prepared in the same manner as Example 1, except that a powder material was used that contained 80 mass% Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 10 mass% WC-12Co (WC cermet) as the second powder, and 10 mass% Mo as the third powder.
[0058] [Example 17] The test piece of Example 17 was prepared in the same manner as Example 1, except that a powder material was used that contained 75 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 15 mass% of WC-12Co (WC cermet) as the second powder, and 10 mass% of Mo as the third powder.
[0059] [Comparative Example 1] A test piece for Comparative Example 1 was prepared in the same manner as in Example 1, except that a powder material containing 100 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder was used.
[0060] [Comparative Example 2] A test piece for Comparative Example 2 was prepared in the same manner as in Example 1, except that a powder material was used that contained 65 mass% of the first powder, Ni-3B-4.4Si (Ni-based self-fluxing alloy), and 35 mass% of the second powder, WC-12Co (WC cermet), of the entire powder material.
[0061] [Comparative Example 3] A test piece for Comparative Example 3 was prepared in the same manner as in Example 1, except that a powder material was used that contained 70 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 10 mass% of WC-12Co (WC cermet) as the second powder, and 20 mass% of Inconel 625 as the third powder.
[0062] [Comparative Example 4] A test piece for Comparative Example 4 was prepared in the same manner as in Example 1, except that a powder material was used that contained 70 mass% Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 15 mass% WC-12Co (WC cermet) as the second powder, and 15 mass% Inconel 625 as the third powder.
[0063] [Comparative Example 5] A test piece for Comparative Example 5 was prepared in the same manner as in Example 1, except that a powder material was used that contained 70 mass% of Ni-3B-4.4Si (Ni-based self-fluxing alloy) as the first powder, 20 mass% of WC-12Co (WC cermet) as the second powder, and 10 mass% of Inconel 625 as the third powder.
[0064] The test pieces obtained in Examples 1 to 17 and Comparative Examples 1 to 5 were subjected to a hardness test (Hv) of the self-fluxing alloy coating, a Suga type abrasion test, and a thermal shock resistance test, as described below.
[0065] [Hardness test] The hardness of the self-fluxing alloy coating was tested using a micro Vickers hardness tester, with measurements being taken at ten points under a load of 300 gf, and the average value was calculated.
[0066] [Suga type abrasion test] The Suga abrasion test for the self-fluxing alloy coating was performed with a load of 3.25 kgf, a rotation speed of 60 rpm, 2000 reciprocations, and SiC#320 test paper. The amount of wear was judged based on the following index, using the measured amount of wear as the standard. ◎: Less than 50 mg. ○: 50 mg or more and less than 100 mg. △: 100 mg or more but less than 200 mg.
[0067] [Thermal shock resistance test] The thermal shock resistance test of the self-fluxing alloy coating consisted of heating the test piece in a high-temperature flame until the surface temperature reached approximately 100-150°C, and then cooling the test piece with water. This process was repeated to check whether peeling of the coating occurred, and the thermal shock resistance was evaluated based on the following indicators. ◯: Peeling occurred after the fourth test or no peeling occurred. △: Peeling occurred on the third try. ×: Peeling occurred on the first or second try.
[0068] Table 3 shows the results of the above tests performed on the test pieces of Examples 1 to 17 and Comparative Examples 1 to 5.
[0069] [Table 3]
[0070] In addition, when the test pieces were observed after each test, it was found that first, multiple cracks appeared on the coating surface, and as the test was repeated, the cracks joined together to form larger cracks, which resulted in the coating peeling off. In this way, multiple cracks joining together to form larger cracks is thought to be one of the causes of coating peeling.
[0071] From the results in Table 3, it was confirmed that in Examples 1 to 14, the wear amount was evaluated as △ or more, and the thermal shock resistance was evaluated as △ or more. Therefore, it was found that the self-fluxing alloy coatings of Examples 1 to 14 have both wear resistance and thermal shock resistance. That is, when the element most abundant in the third powder is Fe, Ni, or Co, it was found that a self-fluxing alloy coating having both wear resistance and thermal shock resistance can be formed by forming a thermal spray coating using a powder material containing 45 to 65 mass% of the first powder, 5 to 35 mass% of the second powder, and 5 to 50 mass% of the third powder, and then performing a fusing process. Note that, since the evaluation was performed strictly in this example, the wear amount evaluation and thermal shock resistance evaluation of some of the examples and comparative examples include △ evaluation, but even the △ evaluation is generally a good result.
[0072] From the results in Table 3, it was confirmed that in Examples 15 to 17, the wear amount was judged to be △ or higher, and the thermal shock resistance was evaluated as ◯ in all cases. Therefore, it was found that the self-fluxing alloy coatings of Examples 15 to 17 have both wear resistance and thermal shock resistance. That is, when the element contained most abundantly in the third powder is Mo, it was found that a self-fluxing alloy coating having both wear resistance and thermal shock resistance can be formed by forming a thermal spray coating using a powder material containing 70 to 85 mass% of the first powder, 5 to 25 mass% of the second powder, and 5 to 25 mass% of the third powder, and then performing a fusing process.
[0073] These results confirmed that a self-fluxing alloy coating having both wear resistance and thermal shock resistance could be formed in any of the following cases: when Inconel 625 was used as the third powder in Examples 1 to 8, when SUS316L was used in Examples 9 to 11, when Stellite 21 was used in Examples 12 to 14, and when Mo was used in Examples 15 to 17.
[0074] On the other hand, from the results of Table 3, it was confirmed that when the powder material is composed of only the first powder as in Comparative Example 1, the thermal shock resistance is rated as ×. Also, from the results of Table 3, it was confirmed that when the powder material does not contain the third powder and contains only the first powder and the second powder in an appropriate amount as in Comparative Example 2, the wear amount is judged as ⊚, while the thermal shock resistance is rated as ×. Furthermore, from the results of Table 3, it was confirmed that when the powder material contains 70 mass% of the first powder as in Comparative Examples 3 to 5, the thermal shock resistance is rated as ×. From these results, it was found that in order to form a self-fluxing alloy coating having both the properties of wear resistance and thermal shock resistance, it is necessary to use a powder material that contains the first powder, the second powder, and the third powder and is adjusted to an appropriate distribution amount.
[0075] From the above results, it was confirmed that a self-fluxing alloy coating having both abrasion resistance and thermal shock resistance can be formed by a manufacturing method for a self-fluxing alloy coating, which includes the steps of spraying a powder material, which is a mixture of appropriate amounts of the first powder, the second powder, and the third powder, onto a substrate to form a thermal sprayed coating on the substrate, and fusing the thermal sprayed coating to form a self-fluxing alloy coating. [Industrial Applicability]
[0076] The method for producing a self-fluxing alloy film according to the present invention can form a self-fluxing alloy film having both abrasion resistance and thermal shock resistance on a substrate, and therefore can be widely used in industrial fields such as steel and non-ferrous metals, etc. In particular, the method can be suitably used in iron-making equipment, pig iron-making equipment, steel-making equipment, non-ferrous metal refining equipment, equipment for hot rolling processes of steel or non-ferrous metals, continuous casting equipment, etc.
Claims
1. a step of spraying a powder material, which is a mixture of a first powder, a second powder, and a third powder, onto a substrate to form a thermal spray coating on the substrate; and fusing the thermal spray coating to form a self-fluxing alloy coating. The first powder is one or more types of self-fluxing alloys selected from the group consisting of Ni-based self-fluxing alloys and Co-based self-fluxing alloys, and the self-fluxing alloys contain 0.8 to 4.5 mass% B and 1.5 to 5.0 mass% Si; The second powder is at least one selected from the group consisting of carbide ceramics and carbide cermets, The third powder is at least one selected from the group consisting of Cr, Mo, Fe, Ni, Co, and alloys having any of them as a main component (however, for alloys having Ni as a main component and alloys having Co as a main component, the Ni-based self-fluxing alloy and the Co-based self-fluxing alloy defined in the first powder are excluded); In the third powder, when the element contained most abundantly by mass is Cr, Fe, Ni, or Co, The powder material is 45 to 65 mass % of the first powder; The second powder is 5 to 35% by weight, and The third powder is contained in an amount of 5 to 50% by mass, In the third powder, when the element contained most abundantly by mass is Mo, The powder material is 70 to 85 mass % of the first powder; 5 to 25% by weight of the second powder, and The third powder is contained in an amount of 5 to 25% by mass. A method for manufacturing a self-fluxing alloy coating.
2. 2. The method of claim 1, wherein the first powder contains 2.5 to 4.0 wt. % B and 3.0 to 5.0 wt. % Si.
3. The method according to claim 1 , wherein the second powder is a tungsten carbide cermet, and the sum of the W content and the C content is 70 mass % or more.
4. The method according to claim 1 , wherein the third powder contains 10 to 30 mass % Cr or 5 to 20 mass % Mo.
5. A method for producing a component part for steel-making equipment, comprising forming a self-fluxing alloy film on a substrate by using the production method according to any one of claims 1 to 4.
6. A method for producing a component part of an iron-making facility, a steel-making facility, or a non-ferrous metal refining facility, comprising forming a self-fluxing alloy coating on a substrate by using the production method according to any one of claims 1 to 4.
7. A method for producing a component part for a hot rolling process of steel or non-ferrous metals, comprising forming a self-fluxing alloy coating on a substrate by using the method according to any one of claims 1 to 4.
8. A method for producing a component part for continuous casting equipment, comprising forming a self-fluxing alloy film on a substrate by using the production method according to any one of claims 1 to 4.
9. A powder material obtained by mixing a first powder, a second powder, and a third powder, The first powder is one or more types of self-fluxing alloys selected from the group consisting of Ni-based self-fluxing alloys and Co-based self-fluxing alloys, and the self-fluxing alloys contain 0.8 to 4.5 mass% B and 1.5 to 5.0 mass% Si; The second powder is at least one selected from the group consisting of carbide ceramics and carbide cermets, The third powder is at least one selected from the group consisting of Cr, Mo, Fe, Ni, Co, and alloys having any of them as a main component (however, for alloys having Ni as a main component and alloys having Co as a main component, the Ni-based self-fluxing alloy and the Co-based self-fluxing alloy defined in the first powder are excluded); In the third powder, when the element contained most abundantly by mass is Cr, Fe, Ni, or Co, The powder material is 45 to 65 mass % of the first powder; The second powder is 5 to 35% by weight, and The third powder is contained in an amount of 5 to 50% by mass, In the third powder, when the element contained most abundantly by mass is Mo, The powder material is 70 to 85 mass % of the first powder; 5 to 25% by weight of the second powder, and The third powder is contained in an amount of 5 to 25% by mass. powder material.
10. The powder material according to claim 9, wherein the first powder contains 2.5 to 4.0 mass% B and 3.0 to 5.0 mass% Si.
11. The powder material according to claim 9, wherein the second powder is a tungsten carbide cermet, and the sum of the W content and the C content is 70 mass% or more.
12. The powder material according to claim 9, wherein the third powder contains 10 to 30 mass% Cr or 5 to 20 mass% Mo.
13. The powder material according to any one of claims 9 to 12, wherein the powder material is a material for self-fluxing alloy thermal spraying.
Citation Information
Patent Citations
Damage resistant and abrasion resistant roll for continuous casting
JP1982203765A
Roll for continuous casting having excellent wear resistance
JP2006263807A
Thermal spray coating
JP2018059174A